2002
DOI: 10.1542/peds.109.6.e90
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Disorder Symptoms in Children and Their Parents After Pediatric Traffic Injury

Abstract: ABSTRACT. Objective. The American Academy of Pediatrics highlights the important role of pediatricians in recognizing adverse child responses to tragic events, such as traffic crashes. One challenge in effectively identifying children and their parents with troubling psychological responses to trauma is that little is known about the normal range of acute psychological responses in children and their parents in the immediate aftermath of traumatic events, making identification of adverse child responses diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 26 publications
4
116
0
1
Order By: Relevance
“…In these instances, personal distress can limit parents' ability to provide adequate care to their children (Winston et al, 2002). However, Finkelhor & Kendall-Tackett (1997) note that it is not parental distress per se that is necessarily detrimental to the child, but more specifically, when the parent's distress overrides or diverts attention away from the needs of the child that children are negatively affected.…”
Section: Dissociation Dissociation Dissociation Dissociation Dissociamentioning
confidence: 99%
“…In these instances, personal distress can limit parents' ability to provide adequate care to their children (Winston et al, 2002). However, Finkelhor & Kendall-Tackett (1997) note that it is not parental distress per se that is necessarily detrimental to the child, but more specifically, when the parent's distress overrides or diverts attention away from the needs of the child that children are negatively affected.…”
Section: Dissociation Dissociation Dissociation Dissociation Dissociamentioning
confidence: 99%
“…79 Unrecognized and untreated, acute stress symptoms can cause lifelong behavioral and mental health problems attributable to changes in neurodevelopment and function. [80][81][82][83][84][85][86] Children with a history of a traumatic experience, be it from unintentional injury, violence, or sexual or physical abuse, can be expected to have more acute stress symptoms in the immediate aftermath of a specific event. 87 Shemesh et al 88 identified PTSD in 29% of the patients in a small convenience sample of pediatric patients who presented to a pediatric ED.…”
Section: Stabilization and Management Of Patients In Psychiatric Crisismentioning
confidence: 99%
“…Attempts to resolve this apparent discrepancy have highlighted the importance of time lapsed between traumatic exposure and assessment [106]. Studies examining acute distress levels soon after the trauma typically find no association between parent and child PTSS [16,137], while longitudinal studies show increases in parent-child PTSS associations over time [79,103,124]. Initial symptoms in the child have been found to impact subsequent symptoms in the parent [79] and initial parent symptoms have been found to predict subsequent child symptoms [31,93,100].…”
Section: Ptsd Runs In Familiesmentioning
confidence: 99%